Misdiagnosed case of scalp arteriovenous malformation - Ozkara, Emre; Özbek, Zühtü; Özdemir, Atilla; Arslantaş, Ali (Asian Journal of Neurosurgery, 2018)
Scalp arteriovenous malformations (AVMs) are abnormal vascular lesions that can be treated safely and effectively, with surgical or endovascular approaches. Because of their complex vascularity, the detailed preoperative evaluation must be carefully performed. Here, we present a case of scalp AVM that required two operations as a result of a misdiagnosis because of inadequate preoperative assessment.
Keywords: Arteriovenous malformation; scalp; surgery